2020
DOI: 10.1101/2020.11.02.20223404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid SARS-CoV-2 Detection by Carbon Nanotube-Based Near-Infrared Nanosensors

Abstract: To effectively track and eliminate COVID-19, it is critical to develop tools for rapid and accessible diagnosis of actively infected individuals. Here, we introduce a single-walled carbon nanotube (SWCNT)-based optical sensing approach towards these ends. We construct a nanosensor based on SWCNTs noncovalently functionalized with ACE2, a host protein with high binding affinity for the SARS-CoV-2 spike protein. Presence of the SARS-CoV-2 spike protein elicits a robust, two-fold nanosensor fluorescence increase … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…PEG was proven to be a suitable polymer for the dispersion of SWCNTs, providing a hydrophilic shell for their stable suspensions in water and biological media and being relatively inert towards protein interaction. 28,49,50 The dendritic architecture exposes four hydrophobic end-groups, enabling non-covalent binding to the SWCNTs. To create a set of polymer-dendrons, two aliphatic and two aromatic end-groups were coupled via an ester group in two different orientations to the dendritic body (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PEG was proven to be a suitable polymer for the dispersion of SWCNTs, providing a hydrophilic shell for their stable suspensions in water and biological media and being relatively inert towards protein interaction. 28,49,50 The dendritic architecture exposes four hydrophobic end-groups, enabling non-covalent binding to the SWCNTs. To create a set of polymer-dendrons, two aliphatic and two aromatic end-groups were coupled via an ester group in two different orientations to the dendritic body (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PEG was proven to be a suitable polymer for the dispersion of SWCNTs, providing a hydrophilic shell for their stable suspensions in water and biological media and being relatively inert towards protein interaction. 28,49,50 The dendritic architecture exposes four hydrophobic end-groups, enabling non-covalent binding to the SWCNTs. To create a set of polymer-dendrons, two aliphatic and two aromatic end-groups were coupled via an ester group in two different orientations to the dendritic body (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An optical nanosensor based on non-covalently functionalized SWCNTs with ACE2 proteins was developed recently ( 62 ). The nanosensor principle depends on the SARS-CoV-2 spike protein presence, which leads to an increase in nanosensor fluorescence within 90 minutes of exposure to the spike protein.…”
Section: Nanoparticle-based Detection Strategies Of Covid-19mentioning
confidence: 99%
“…Sensor responded in the salivary samples and virus transport environments. It is shown that ACE2-SWCNT nanosensors retain detection capability in a modified surface with a 73% fluorescence turn-on response within 5 seconds of exposure to 35 mg/L SARS-CoV-2 virus-like particles ( 62 ).…”
Section: Nanoparticle-based Detection Strategies Of Covid-19mentioning
confidence: 99%